Good night dozers - Gamble, Adam; Jasper, Mark; Kelly, Cooper ([Place of publication not identified] : Good Night Books, 2017)
Throughout a busy day, different kinds of bulldozers complete a variety of tasks, sometimes working with other construction equipment.
On board pages.
Keywords: Construction equipment -- Juvenile fiction